A PLG/HAp composite scaffold for lentivirus delivery - Boehler, RM (2013)
Gene delivery from tissue engineering scaffolds provides the opportunity to control the microenvironment by inducing expression of regenerative factors. Hydroxyapatite (HAp) nanoparticles can bind lentivirus, and we investigated the incorporation of HAp into poly(lactide-co-glycolide) (PLG) scaffolds in order to retain lentivirus added to the scaffold. PLG/HAp scaffolds loaded with lentivirus enhanced transgene expression over 10-fold in vitro relative to scaffolds without HAp. Following in vivo implantation, PLG/HAp scaffolds promoted transgene expression for more than 100 days, with the level and duration enhanced relative to control scaffolds with lentivirus/HAp complexes added to PLG scaffolds. The extent of HAp incorporated into the scaffold influenced transgene expression, in part through its impact on porous architecture. Expression in vivo was localized to PLG/HAp scaffolds, with macrophages the primary cell type transduced at day 3, yet transduction of neutrophils and dendritic cells was also observed. At day 21 in PLG/HAp scaffolds, non-immune cells were transduced to a greater extent than immune cells, a trend that was opposite results from PLG scaffolds. Thus, in addition to retaining the virus, PLG/HAp influenced cell infiltration and preferentially transduced non-immune cells.